Structure, ferroelectric/magnetoelectric properties and leakage current density of (Bi0.85Nd0.15)FeO3 thin films - Simões, Alexandre Zirpoli [UNESP]; Cavalcante, L. S. [UNESP]; Moura, F.; Longo, Elson [UNESP]; Varela, José Arana [UNESP] (Elsevier B.V. Sa, 2011)
In this paper, we report on the structure, ferroelectric/magnetoelectric properties and improvement of leakage current density of (Bi0.85Nd0.15)FeO3 (BNFO) thin films deposited on Pt(1 1 1)/Ti/SiO2/Si substrates from the polymeric precursor method. X-ray patterns and Rietveld refinement indicated that BNFO thin films with a tetragonal structure can be obtained at 500 degrees C for 2 h in static air. Field emission scanning electron, atomic force and piezoelectric force microscopies showed the microstructure, thickness and domains with polarization-oriented vectors of BNFO thin films. Ferroelectric and magnetoelectric properties are evident by hysteresis loops. The magnetoelectric coefficient measurement was performed to show the magnetoelectric coupling behavior. The maximum magnetoelectric coefficient in the longitudinal direction was close to 12 V/cm Oe. Piezoresponse force microscopy micrographs reveal a polarization reversal with 71 degrees and 180 degrees domain switchings and one striped-domain pattern oriented at 45 degrees besides the presence of some nanodomains with rhombohedral phase involved in a matrix with tetragonal structure. The cluster models illustrated the unipolar strain behavior of BNFO thin films. The leakage current density at 5.0V is equal to 1.5 x 10(-10) A/cm(2) and the dominant mechanism in the low-leakage current for BNFO thin films was space-charge-limited conduction. (C) 2011 Elsevier B.V. All rights reserved.
Keywords: Ferroelectrics; Chemical synthesis; Piezoelectricity; Magnetic measurements